Toward an evolutionary regime for spectrum governance : licensing or unrestricted entry? - Baumol, William J. (AEI-Brookings Joint Center for Regulatory Studies, 2006)
"Evaluates two options for spectrum governance--a tradable license approach and a commons approach--in terms of interference, investment in innovation, monopoly power, diversity, rural service, and vested interests versus adaptability"--Provided by publisher